Synthesis of polylactide by ring opening polymerization. Part B - Structure and Products properties. - Tiến, Mai Văn; Trinh, Phạm Thế; Cường, Ngô Duy; Hảo, Nguyễn Hường (Vietnam Journal of Chemistry, 2012)
Homopoly(lactide) was synthesized from cyclic dimers DL-lactide or LL-lactide, by ring opening polymerization in the presence of catalyst stannous octoate and chain control agent lauryl ancohol. The effect of lactide type to properties of PLA were studied. The molecular weight was determined by intrisic viscosity measurement and gel permenation chromatography (GPC). The polymers were further characterized by IR, 1H-NMR; 13C-NMR and DSC, TGA, and X-ray diffraction.